[tex]x = \frac{-11}{3}[/tex]
Step-by-step explanation:
Here we have , If the first step in the solution of the equation 2x - 8 = 5x + 3 is "subtract 2x," then in the form of a paragraph, explain in complete sentences the next steps necessary to completely solve the equation for x. Let's solve this :
2x - 8 = 5x + 3
⇒ [tex]2x - 8 = 5x + 3[/tex]
⇒ [tex](2x - 8)-2x = (5x + 3)-2x[/tex] { subtract 2x from both side }
⇒ [tex]0 - 8 = 5x-2x + 3[/tex]
⇒ [tex]- 8 = 3x + 3[/tex]
⇒ [tex]- 8 -3= 3x + 3-3[/tex] { subtract 3 from both sides }
⇒ [tex]- 11 = 3x + 0[/tex]
⇒ [tex]- 11 = 3x[/tex]
⇒ [tex]\frac{-11}{3} = \frac{3}{3} x[/tex] { divide 3 from both sides }
⇒ [tex]x = \frac{-11}{3}[/tex]